COMPARATIVE ANALYSIS OF THE MOTIVATIONAL COMPONENT OF THE INDUSTRY-OUTPUT TARIFF AGREEMENTS IN THE INDUSTRIES OF FUEL & ENERGY COMPLEX - A. V. Akopyan; N. G. Lubimova (Вестник университета)
Industry tariff agreements have been studied from the point of view of the motivational component of staff labor in organizations of the fuel and energy complex. Criteria of comparison have been selected and the optimal labor motivation strategy in the oil, gas, coal and electric power industries has been revealed. Features and similar approaches in the organization of the motivation of the industries of the fuel and energy complex have been identified. World experience of the labor motivation in the fuel and energy industries, such as in the USA, Japan and in Europe has been examined in comparison with domestic practice in these sectors.